2012
DOI: 10.1038/mp.2012.115
|View full text |Cite
|
Sign up to set email alerts
|

Latrepirdine stimulates autophagy and reduces accumulation of α-synuclein in cells and in mouse brain

Abstract: Latrepirdine (Dimebon; dimebolin) is a neuroactive compound that was associated with enhanced cognition, neuroprotection, and neurogenesis in laboratory animals, and has entered phase II clinical trials for both Alzheimer’s (AD) and Huntington’s diseases (HD). Based on recent indications that latrepirdine protects cells against cytotoxicity associated with expression of aggregatable neurodegeneration-related proteins, including Aβ42 and γ-synuclein, we sought to determine whether latrepirdine offers protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 35 publications
1
63
0
Order By: Relevance
“…Similar observations have been noted with agents such as trehalose that promote autophagy in a TORindependent manner 91 . Latreperdine (Dimebon®) is an antihistamine that has been widely used in Russia and promotes autophagy and clearance of α-synuclein 92 . Latreperdine been tested in short-term clinical trials in AD and failed to meet the primary endpoint, but was well tolerated with no significant toxicity.…”
Section: Therapies Targeting Pathways Implicated By Genetic Studiesmentioning
confidence: 99%
“…Similar observations have been noted with agents such as trehalose that promote autophagy in a TORindependent manner 91 . Latreperdine (Dimebon®) is an antihistamine that has been widely used in Russia and promotes autophagy and clearance of α-synuclein 92 . Latreperdine been tested in short-term clinical trials in AD and failed to meet the primary endpoint, but was well tolerated with no significant toxicity.…”
Section: Therapies Targeting Pathways Implicated By Genetic Studiesmentioning
confidence: 99%
“…In contrast, Dimebon's suppression of TBHP-induced lipid peroxidation is maximal at 0.4 mM [13]. Moreover, Dimebon decreased mitochondrial lipid peroxidation induced by calcium and amyloid β-peptide (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in contrast to cyclosporine A [13,14] and decreased spontaneous lipid peroxidation in rat brain homogenates (Fig. 4), indicative of an anti-aging component.…”
Section: Dimebon Contributes To Mitochondrial Stabilizationmentioning
confidence: 88%
“…Bharadwaj et al similarly found that Dimebon facilitated removal of Aβ42-GFP levels via the autophagy pathway in yeast [24]. Chronic administration of Dimebon reportedly induced autophagy and α-synuclein removal in mouse brain [26].…”
Section: Induction Of Autophagymentioning
confidence: 94%
See 2 more Smart Citations